Crystal structure of catena-poly[diaqua-bis(μ2-ethane-1,2-diyl-bis(pyridine-3-carboxylate-κ2N:N′))copper(II)] dinitrate, C28H28CuN6O16 - Brito Iván (Zeitschrift für Kristallographie - New Crystal Structures, 2017)
C28H28CuN6O16, triclinic, P1̅, (no. 2), a = 7.3118(7) Å, b = 10.0597(8) Å, c = 11.2579(10) Å, α = 92.109(7)°, β = 105.804(7)°, γ = 98.416(7)°, V = 785.63(12)Å3, Z = 1, Rgt(F) = 0.042, wRref(F2) = 0.095, T = 173(2) K.